Training Method on the Passing Accuracy of Basketball by Modified Small-Sided Games for Physical Education Senior High School - Roas Irsyada; Hasna Tri Oktavia (FKIP Universitas Lampung, 2026)
This study was motivated by the low level of basketball passing accuracy among students in Physical Education classes at Senior High Schools in Magelang Regency, Central Java. Passing is a fundamental technical skill in basketball that significantly influences offensive organization and overall team performance. Therefore, this study aimed to examine the effect of Small-Sided Games (SSG) modifications, specifically the 2×2 and 4×4 formats, on students’ basketball passing accuracy and to compare the effectiveness of both formats. This study employed a quasi-experimental method with a Two-Group Pretest–Posttest Design. The participants were 32 tenth-grade students selected via convenience sampling and assigned to two groups using a matched-subjects procedure based on pretest scores. The intervention was conducted over eight weeks with two training sessions per week. Passing accuracy was measured using a validated basketball passing accuracy test. Data were analyzed using descriptive statistics, Shapiro–Wilk normality tests, Levene’s homogeneity tests, paired-sample t-tests, independent-sample t-tests, and Cohen’s d effect size analysis. Both SSG formats significantly improved students’ passing accuracy. In the 2×2 SSG group, the mean score increased from 8.8 to 16.6 (p < 0.001), while in the 4×4 SSG group, the mean score increased from 11.0 to 13.9 (p = 0.008). Furthermore, the independent-samples t-test revealed a significant difference between groups (t = 4.55, p < 0.001), indicating that the 2×2 format produced greater improvement than the 4×4 format. Effect size analysis also showed a large effect for the 2×2 group (d = 1.84) and a moderate-to-large effect for the 4×4 group (d = 0.77). Small-Sided Games training significantly improves basketball passing accuracy among high school students. However, the 2×2 format is more effective than the 4×4 format in enhancing individual technical performance, particularly passing accuracy, due to increased ball contacts and decision-making opportunities. Keywords: accuracy, basketball, small-sided games.